Melanopsin—Shedding Light on the Elusive Circadian Photopigment - Brown, R. Lane (2004)
Circadian photoentrainment is the process by which the brain’s internal clock becomes synchronized with the daily external cycle of light and dark. In mammals, this process is mediated exclusively by a novel class of retinal ganglion cells that send axonal projections to the suprachiasmatic nuclei (SCN), the region of the brain that houses the circadian pacemaker. In contrast to their counterparts that mediate image-forming vision, SCN-projecting RGCs are intrinsically sensitive to light, independent of synaptic input from rod and cone photoreceptors. The recent discovery of these photosensitive RGCs has challenged the long-standing dogma of retinal physiology that rod and cone photoreceptors are the only retinal cells that respond directly to light and has explained the perplexing finding that mice lacking rod and cone photoreceptors can still reliably entrain their circadian rhythms to light. These SCN-projecting RGCs selectively express melanopsin, a novel opsin-like protein that has been proposed as a likely candidate for the photopigment in these cells. Research in the past three years has revealed that disruption of the melanopsin gene impairs circadian photoentrainment, as well as other nonvisual responses to light such as the pupillary light reflex. Until recently, however, there was no direct demonstration that melanopsin formed a functional photopigment capable of catalyzing G-protein activation in a light-dependent manner. Our laboratory has recently succeeded in expressing melanopsin in a heterologous tissue culture system and reconstituting a pigment with the 11-cis-retinal chromophore. In a reconstituted biochemical system, the reconstituted melanopsin was capable of activating transducin, the G-protein of rod photoreceptors, in a light-dependent manner. The absorbance spectrum of this heterologously expressed melanopsin, however, does not match that predicted by previous behavioral and electophysiological studies. Although melanopsin is clearly the leading candidate for the elusive photopigment of the circadian system, further research is needed to resolve the mystery posed by its absorbance spectrum and to fully elucidate its role in circadian photoentrainment.